2021
DOI: 10.12998/wjcc.v9.i25.7358
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic analysis of clinical coronary heart disease and coronary artery disease concerning young and middle-aged male patients

Abstract: BACKGROUND Coronary heart disease (CHD) is a type of coronary atherosclerotic heart disease. In recent years, the incidence of CHD has been increasing annually, with an increasing number of young patients. Severe CHD may cause severe myocardial ischemia or myocardial necrosis, which in turn may cause myocardial infarction and related complications that seriously affect the life and health of the patient. AIM To examine the coronary arteries and clinical features of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This study showed that from 1990 to 2019, the disease burden of IHD in Chinese people aged ≥70 years has significantly increased, with a peak in people aged ≥80 years. The death rate and DALYs of IHD in the Chinese population aged 20–54 years were higher in 2019 than in 1990, which is consistent with previous research findings that the rates of IHD incidence and death in China show an increasing trend in younger people ( 18 , 19 ) as a result of overweight, smoking, abnormal lipid metabolism, high blood uric acid, inflammatory response, and impaired vascular endothelial function in young and middle-aged people ( 20 ).…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that from 1990 to 2019, the disease burden of IHD in Chinese people aged ≥70 years has significantly increased, with a peak in people aged ≥80 years. The death rate and DALYs of IHD in the Chinese population aged 20–54 years were higher in 2019 than in 1990, which is consistent with previous research findings that the rates of IHD incidence and death in China show an increasing trend in younger people ( 18 , 19 ) as a result of overweight, smoking, abnormal lipid metabolism, high blood uric acid, inflammatory response, and impaired vascular endothelial function in young and middle-aged people ( 20 ).…”
Section: Discussionsupporting
confidence: 90%
“…Most of the cholesterol in the human body exists and is transported in the form of binding to lipoproteins and then transported to various parts of the body to play corresponding roles [ 3 ]. Studies have shown that the elevated contents of total cholesterol and LDL-C in the blood circulation are related to coronary atherosclerosis [ 9 ]. Monitoring LDL-C level is the core strategy of the guidelines for the treatment of dyslipidemia at home and abroad [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some impersonal factors, such as diabetes, BMI, and hypertension, have been watched to be closely related to CHD [21][22][23], numerous types of research have shown that alcohol consumption and smoking are significantly associated with CHD [24,25]. Furthermore, some common demographic characteristics, such as marital status, gender, race, and age, are also closely related to CHD [26,27].…”
Section: Introductionmentioning
confidence: 99%